STRATEGI PENINGKATAN MOTIVASI BELAJAR ANAK MELALUI PENDEKATAN KOMUNIKASI PERSUASIF - Salas, Adhika Yovaldi (Politeknik Ilmu Pemasyarakatan, 2025)
The current wave of globalization is getting stronger and has a bad impact on children. The growth of children today cannot be separated from the many bad influences of globalization that are not filtered properly so that many children fall into criminal acts that violate the law. Most children who are in conflict with the law must be expelled from formal schools because they are considered to be a bad influence on their friends. This phenomenon is a problem that cannot be ignored because education for children must be a priority for the government. To follow up on this matter, The Indonesian Government has enacted Law no. 11 of 2012 concerning the Juvenile Criminal Justice System. As well as Law no. 35 of 2014 concerning Child Protection, renewing Law no. 23 of 2002 concerning Child Protection. This study intends to understand the description of persuasive communication strategies applied by correctional officers and tutors in increasing children's learning motivation at the Class I Kutoarjo Child Special Guidance Institute (LPKA). This study uses a single case study that puts forward a descriptive qualitative method in which the data is collected through observation, literature study, and interviews with selected informants. Data analysis in this study used the interactive method of Huberman and Saldana which included four stages of research consisting of: data collection, data reduction, data representation, and conclusion drawing or verification. The research conducted illustrates that in the implementation of strategies to increase children's learning motivation in LPKA Class I Kutoarjo it has been running quite optimally, children's motivation in learning is quite good. The implementation of strategies to increase learning motivation through a persuasive communication approach provides benefits for children in providing coaching programs at LPKA. With the application of persuasive communication by officers and tutors, children's motivation in learning can be increased so that they are able to achieve the specified educational competency standards.